Cytological evaluation of lymphoepithelial lesions of the major salivary glands with special reference to lymphoepithelial sialadenitis: A clinicopathological study - Rajashree Pradhan; Sajeeb Mondal; Chirasri Goswami; Suman Chatterjee (Asian Journal of Medical Sciences, 2025)
Background: Fine needle aspiration cytology (FNAC) is an accurate, reliable, minimally invasive, and cost-effective procedure for pre-operative evaluation of salivary gland lesions. Salivary glands are host to a wide range of pathological conditions ranging from reactive, inflammatory, and cystic conditions to neoplastic lesions. In comparison to the epithelial lesions, salivary gland lymphoepithelial lesions (LELs) are rare. Cytological evaluation of the salivary gland LELs was described as case reports in few literatures. Aims and Objectives: The current study aimed to discuss cytological features of the LELs of the salivary gland elaborately. Materials and Methods: The study was conducted over a period of 5 years in which a total of 720 salivary gland FNAC samples along with their clinical presentations were studied. LELs were diagnosed in 36 cases. Results: Out of these lymphoepithelial cysts were diagnosed in 5 cases (13.88%), lymphoepithelial sialadenitis in 16 (44.44%), suggestive of lymphoepithelial carcinoma in 2 (5.5%), and lymphoepithelial sialadenitis with close differential diagnosis such as chronic sclerosing sialadenitis (7,19.44%), Warthin’s tumor (4,10.11%), and low-grade lymphoma in rest of the cases (2,5.5%). Conclusion: LELs are rare lesions of the salivary gland characterized by lymphocyte infiltration into the salivary parenchyma with associated salivary ductal epithelial cell proliferation. These lesions include reactive non-neoplastic lesions to benign and malignant lesions whose clinical significance varies greatly among these lesions. Hence, careful history taking, clinical examination findings, and adequate sampling for cytological evaluation play pivotal role in a conclusive diagnosis preoperatively which leads to better patient management.